Implementasi Kurikulum al-Syahadah al-Ulya Ulul Albab Melalui Kitab Bidayah al-Hidayah dalam Kerangka Pemikiran Tasawuf al-Ghazali: Implementation of al-Shayadah al-Ulya Ulul Albab Curriculum Through the Book of Bidayah al-Hidayah in the Framework of al-Ghazali’s Sufism Thought - Shamsuddin, Ahmad Handhalas; Sa’ari, Che Zarrina; Zainal Abidin, Mohd Syukri (Jurnal Usuluddin, 2024)
The Malaysian Ministry of Education (MOE) has made strides in dignifying turath education in the mainstream curriculum in 2018. The turath curriculum is called the al-Syahadah al-Ulya Ulul Albab Curriculum (SUUA) which is currently implemented at Sekolah Menengah Imtiaz Yayasan Terengganu, Besut, Terengganu (SMIYTB). The SUUA curriculum is also a continuation of the Tahfiz Integrated Curriculum (KBT) which started in 2014 for selected students. In the SUUA Curriculum, there are Islamic Studies subjects that contain 4 main areas, namely the Tawhid, Fiqh, Akhlak and Sirah. Akhlak is a field of sufism that uses the book Bidayah al-Hidayah written by al-Ghazali as a curriculum according to the appropriateness that has been outlined. Al-Ghazali is a very famous figure in the Malay world, especially in the field of sufism. His writing is used as a curriculum, teaching and learning material, research and practiced by the community in the Malay world. The SUUA Curriculum, especially in the field of sufism, is very important in the development of students’ morals and values as a generation of ulama. This study was conducted to see the comparison of the SUUA Curriculum in the subjects of Turath Dirasat Islamiah, especially the field of akhlak with the book of Bidayah al-Hidayah. The study was conducted qualitatively with research on literature and document analysis. The results of the study found that in the SUUA Curriculum at SMIYTB through the subject of Turath Dirasat Islamiah in the field of akhlak, al-Ghazali’s thought is implemented through the book Bidayah al-Hidayah to students. However, it was implemented selectively because the introductory chapter, the third chapter and the closing chapter were not placed from the original content of the book Bidayah al-Hidayah. Therefore, there is a need and recommendation to include the introductory chapter, the third chapter and the closing chapter from the original content of the book Bidayah al-Hidayah into the SUUA curriculum so that students can implement al-Ghazali’s thought which is suitable for the upper secondary level